Cattle Preference for Annual Forages - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2019)
Many plant species that are available to use as cover crops also have potential as forage for cattle. With this array of options it can be daunting to decide which plants to establish to meet goals as either a cover crop, forage, or for both. Therefore, the purpose of this study was to identify the annual forages fed to cattle in the fall, winter, or summer that cattle preferred. To summarize, grasses were the most highly preferred forage for cattle regardless of grazing period. Low glucosinolate brassicas such as ‘Graza’ forage radish was the most highly preferred brassica that was offered. Selection by cattle of legume and broadleaf plant species was variable, and was primarily driven by other less-preferred plants that were offered.
Keywords: forage; selectivity; behavior